Can blockchain payment services influence customers' loyalty intention in the hospitality industry? A mediation assessment - Rashed Al Karim; Md Karim Rabiul; Mahima Ishrat; Pornpisanu Promsivapallop; Sakia Kawser (Administrative Sciences, 2023)
This study analyzes the impact of blockchain mobile payment services on customer loyalty intention through the mediating role of service quality, privacy and security, and customer satisfaction in the Bangladeshi hospitality industry. Data were collected through a survey using a structured questionnaire from 326 respondents who stayed in 4- and 5-star hotels in Chattogram and Cox's Bazar. Respondents' (N = 326) opinions were analyzed employing Smart PLS software. The results ensure that privacy and security and customer satisfaction mediate the blockchain-based mobile payment services and loyalty intention relationship. However, service quality does not mediate that relationship. The findings of the mediation effect of privacy and security and customer satisfaction are a unique contribution to the blockchain literature in the field of the hospitality industry. Hoteliers are encouraged to employ appropriate blockchain mobile payment services for better quality customer service and ensured safety and security, and in turn, loyalty intention.
Keywords: 350; blockchain mobile payment service; customer satisfaction; loyalty intention; privacy and security; service quality